Effect of systemic lupus erythematosus on pregnancy outcome: a study of 40 cases at a tertiary health care center - Pereira, Brynivalentina James; Patel, Babulal S.; Shah, Akshay C.; Parikh, Purvi M.; Kumar, Mahima M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Systemic lupus erythematosus (SLE) is a multisystem autoimmune disease in which organs and cells undergo damage initially mediated by tissue-binding autoantibodies and immune complexes. SLE has an impact on various organ systems. Ninety percent of the patients are women of child-bearing age thus pregnancies and its outcomes are of particular importance among women with SLE. The current study aims to study the maternal and foetal outcomes in SLE patients and to identify the predictors of adverse maternal and foetal outcomes in pregnancy. Methods: Data of 60 pregnancies of 40 female SLE patients from September 2019 to May 2021 in V. S. general hospital, Ahmedabad, were retrospectively reviewed. All the patients met the 2012 SLICC classification criteria for SLE. SLE disease activity in pre-pregnancy state and during pregnancy were retrospectively evaluated using SLE disease activity index-(SLEDAI), based on medical history, physical examination and immunological evaluation. SLE disease activity during the current non pregnant state was also calculated using SLEDAI. Results: In our study carried out 3 years among 60 pregnancies, the disease flared up in 23 pregnancies (38.3%). Out of 60 pregnancies with SLE, there 17 (28.3%) unfavourable outcomes. Unfavourable outcomes were significantly higher in patients with SLE flare (14, 60.9%). Similarly, patients with lupus nephritis (8, 66.7%) had unfavourable outcome. Conclusions: In spite of tertiary level care in the hospital, foetal loss is a significant risk in these patients, so proper periconceptional counselling should be done